2021
DOI: 10.3389/fphy.2020.625424
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive Time-Gated Fluorescence Immunoassay Platform Using Mn-Doped AgZnInS/ZnS Nanocrystals as Signal Transducers

Abstract: In this work, a time-gated immunoassay platform using low-energy excitable and fluorescence long-lived Mn:AgZnInS/ZnS nanocrystals as signal transducers was developed and applied to the detection of the capsular polysaccharide (CPS) of Burkholderia pseudomallei, a Gram-negative bacterium that is the causative agent of melioidosis. CPS is a high molecular weight antigen displayed and is shed from the outer membrane of B. pseudomallei. The immunoassay using the time-gated platform presents a limit of detection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Following this work, Gallian et al modified the optical path of their instrument, as shown in Figure 16A,B, and made the instrument able to read signals from the microwell of a microplate. 153 They then performed a micromagnetic beadbased immunoassay to detect capsular polysaccharide (CPS) of Burkholderia pseudomallei, which is a biomarker for pathogen infection. In the immunoassay, they used monoclonal antibody (mAb 4C4)-coated magnetic beads to capture CPS in PBS with 5% milk or human serum, and after washing, they used 4C4−NC conjugates as probes to label the captured CPS.…”
Section: Surface Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Following this work, Gallian et al modified the optical path of their instrument, as shown in Figure 16A,B, and made the instrument able to read signals from the microwell of a microplate. 153 They then performed a micromagnetic beadbased immunoassay to detect capsular polysaccharide (CPS) of Burkholderia pseudomallei, which is a biomarker for pathogen infection. In the immunoassay, they used monoclonal antibody (mAb 4C4)-coated magnetic beads to capture CPS in PBS with 5% milk or human serum, and after washing, they used 4C4−NC conjugates as probes to label the captured CPS.…”
Section: Surface Modificationmentioning
confidence: 99%
“…Following this work, Gallian et al modified the optical path of their instrument, as shown in Figure A,B, and made the instrument able to read signals from the microwell of a microplate . They then performed a micromagnetic bead-based immunoassay to detect capsular polysaccharide (CPS) of Burkholderia pseudomallei , which is a biomarker for pathogen infection.…”
Section: Applications Of Mn-doped Ncs In Time-resolved Luminescence B...mentioning
confidence: 99%
See 1 more Smart Citation
“…Long‐lived luminescence probes with lifetimes in the microsecond‐to‐millisecond range, together with time‐resolved luminescence detection, offer high‐contrast detection of targets without confounding background from biological autofluorescence and residual excitation light. This concept, first proposed for immunoassays in the mid‐1970s, [1] has been widely demonstrated for accurate detection and quantification of proteins, [2–3] nucleic acids, [4] molecular biomarkers, [5–6] and pathogens [7–9] . The technique has been successfully implemented in various analytical platforms for testing liquid samples, [10] solid substrates, [11] cultured cells, [12–13] extracted tissues, [14] and small animals in vivo [15–17] .…”
Section: Introductionmentioning
confidence: 99%